2022
DOI: 10.1111/jce.15715
|View full text |Cite
|
Sign up to set email alerts
|

Women are underrepresented in cardiac resynchronization therapy trials

Abstract: Introduction Current guidelines for cardiac resynchronization therapy (CRT) device implant are the same across both sexes however women have been traditionally underrepresented in randomized controlled trials (RCTs). We aimed to identify if the number of women included in CRT trials is representative of the real‐world burden of heart failure (HF) in women. Methods RCTs evaluating the benefit of CRT in HF patients referenced in the 2012 EHRA/HRS expert consensus statement on CRT in HF were included. Studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Importantly, we report results from the largest dataset of female CRT patients ever evaluated so far. (14) Our findings were as follows: CRT response was superior in females in the overall cohort . In the NICM LBBB cohort , female sex was not an independent response predictor. In the NICM LBBB cohort, increasing normalised QRSd is a significant independent response predictor. In the NICM LBBB cohort , CRT response was superior in females at QRSd < 150 ms and the association between normalised QRSd and response is strongest at QRSd <150ms. …”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Importantly, we report results from the largest dataset of female CRT patients ever evaluated so far. (14) Our findings were as follows: CRT response was superior in females in the overall cohort . In the NICM LBBB cohort , female sex was not an independent response predictor. In the NICM LBBB cohort, increasing normalised QRSd is a significant independent response predictor. In the NICM LBBB cohort , CRT response was superior in females at QRSd < 150 ms and the association between normalised QRSd and response is strongest at QRSd <150ms. …”
Section: Discussionmentioning
confidence: 50%
“…Determining this accurately requires examination of large sample sizes, especially as women represent only 20-30% of the population in CRT trials. (14) Sex-related CRT response disparity may also be explained by differences in cardiac size, (15) that is, that females are relatively smaller than males, and therefore have a greater degree of dyssynchrony at a given QRSd. This is supported by studies that report that females exhibit an improved CRT response compared to males in cohorts with a QRSd <150ms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior somewhat smaller study from the Swedish heart failure registry showed similar results on de novo CRT implants; a lower proportion of CRT use in women, but also equal underutilization for men 12 . Even though women have notoriously been underrepresented in the clinical trials, there is no evidence to support that the CRT effect women should be less favorable than for men 13 . On the contrary, several trials and meta‐analyses have found that (in de novo CRT implants) women have more pronounced reverse remodeling response, quality of life improvement and better survival free of heart failure hospitalization 14–16 .…”
Section: Discussionmentioning
confidence: 94%
“…12 Even though women have notoriously been underrepresented in the clinical trials, there is no evidence to support that the CRT effect women should be less favorable than for men. 13 On the contrary, several trials and meta-analyses have found that (in de novo CRT implants) women have more pronounced reverse remodeling response, quality of life improvement and better survival free of heart failure hospitalization. [14][15][16] The potential reasons for more favorable response in women are several; in some studies, they had higher percentage of biventricular pacing, and some have suggested that for a given QRS duration women have relatively more LV dyssynchrony amenable to correction.…”
Section: Importance Of Crt Upgrade and Potential Sex Biasmentioning
confidence: 99%